Variations in the Median Cubital Vein: A Conceptual Review - Akhil , Jakkula; Sontakke , Yogesh Ashok; Kumar , Dinesh V (Academia Anatomica International, 2021)
The median cubital vein, connecting the basilic and cephalic veins in the cubital fossa, is used for routine clinical procedures such as phlebotomy, insertion of intravenous cannulas, critical investigations, cardiac angiography and stent placement. Numerous variations regarding the arrange- ment of the median cubital vein are mentioned in the literature, such as classical or N-type, M-type, I-type, absence of cephalic vein in the arm, doubled median cubital vein, median cubital vein as the venous arch. In majority of the population either classical type or N-type variation has been documented. Significant percentage of the population have an absence of median cubital vein, replaced by the median cephalic and median basilic veins. Geographical differences in frequencies of variations of the median cubital vein have also been documented. In the background of the clinical utility, it rises paramount importance for medical personnel to know about the anatomical variations of the cubital vein. Lack of awareness would incur needless harm and suffering to the patient and delay investigation and treatment modalities. Therefore, we intend to do a comprehensive review of the variations in the median cubital vein.